Validity and reliability of a new method for measuring putting stroke kinematics using the TOMI® system - Mackenzie, S. J.; Evans, D. B. (Journal of Sports Sciences, 2010)
The purpose of this study was to determine the validity and reliability of a new method for measuring three-dimensional (3D) putting stroke kinematics using the TOMI® device. A putting robot and a high-speed camera were used to simultaneously collect data for the validity evaluation. The TOMI® device, when used in conjunction with standard 3D coordinate data processing techniques, was found to be a valid and reliable method for measuring face angle, stroke path, putter speed, and impact spot at the moment of ball contact. The validity of the TOMI® measurement system was quantified using the 95% limits of agreement method for each aforementioned variable. The practical significance of each validity score was assessed by incorporating the maximum estimated measurement error into the stroke of the putting robot for 10 consecutive putts. All putts were executed from a distance of 4 m on a straight and flat synthetic putting surface. Since all putts were holed successfully, the measurement error for each variable was deemed to be negligible for the purposes of measuring putting stroke kinematics. The influence of key kinematic errors, at impact, on the outcome of a putt was also determined.